Тенденції антиформалізму та цінностей у сучасній юриспруденції - Дудченко, Валентина Віталіївна; Дудченко, Валентина Витальевна; Dudchenko, Valentina (My University, 2012)
In article author proves that the dominant trend in the modern jurisprudence is an integrative legal thinking, when law combines the ideas (metaphysics), facts (positivism) and values (axiology). Ontology of law as a Eidos theory is proved. Syncretism of law, ethics and religion, legitimation of law, subsidiary character of positive law are shown.
Дудченко В. В. Тенденції антиформалізму та цінностей у сучасній юриспруденції / В. В. Дудченко // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2012. – Т. 11. – С. 225-234.
Keywords: антиформалізм у праві; цінності; інтегративне праворозуміння; ідеї; факти; оцінки; легітимація; субсидіарний характер позитивного права; синкретизм права; антиформализм в праве; ценности; интегративное правопонимание; идеи; факты; оценки; легитимация; субсидиарный характер позитивного права; antiformalizm in law; valuables; integrative legal thinking; ideas; facts; evaluation; legitimation; subsidiary character of positive law; syncretism of law